Durable 5-year local control for resected brain metastases with early adjuvant SRS: the effect of timing on intended-field control. Issue 3 (21st January 2021) - Bander, Evan D; Yuan, Melissa; Reiner, Anne S; Panageas, Katherine S; Ballangrud, Åse M; Brennan, Cameron W; Beal, Kathryn; Tabar, Viviane; Moss, Nelson S
Abstract: Background: Adjuvant stereotactic radiosurgery (SRS) improves the local control of resected brain metastases (BrM). However, the dependency of long-term outcomes on SRS timing relative to surgery remains unclear. Methods: Retrospective analysis of patients treated with metastasectomy-plus-adjuvant SRS at Memorial Sloan Kettering Cancer Center (MSK) between 2013 and 2016 was conducted. Kaplan-Meier methodology was used to describe overall survival (OS) and cumulative incidence rates were estimated by type of recurrence, accounting for death as a competing event. Recursive partitioning analysis (RPA) and competing risks regression modeling assessed prognostic variables and associated events of interest. Results: Two hundred and eighty-two patients with BrM had a median OS of 1.5 years (95% CI: 1.2-2.1) from adjuvant SRS with median follow-up of 49.8 months for survivors. Local surgical recurrence, other simultaneously SRS-irradiated site recurrence, and distant central nervous system (CNS) progression rates were 14.3% (95% CI: 10.1-18.5), 4.9% (95% CI: 2.3-7.5), and 47.5% (95% CI: 41.4-53.6) at 5 years, respectively. Median time-to-adjuvant SRS (TT-SRS) was 34 days (IQR: 27-39). TT-SRS was significantly associated with surgical site recurrence rate ( P = 0.0008). SRS delivered within 1 month resulted in surgical site recurrence rate of 6.1% (95% CI: 1.3-10.9) at 1-year, compared to 9.2% (95% CI: 4.9-13.6) if delivered between 1 and 2 months, or 27.3% (95% CI: 0.0-55.5) if delivered >2 months after surgery. OS was significantly lower for patients with TT-SRS >~2 months. Postoperative length of stay, discharge to a rehabilitation facility, urgent care visits, and/or disease recurrence between surgery and adjuvant SRS associated with increased TT-SRS. Conclusions: Adjuvant SRS provides durable local control. However, delays in initiation of postoperative SRS can decrease its efficacy.